A tissue‐engineered, decellularized, connective tissue membrane for allogeneic arterial patch implantation. Issue 4 (12th November 2021) - Yamanami, Masashi; Kanda, Keiichi; Morimoto, Kazuki; Inoue, Tomoya; Watanabe, Taiji; Sakai, Osamu; Kami, Daisuke; Gojo, Satoshi; Yaku, Hitoshi
Abstract: Background: We have previously applied in vivo tissue‐engineered vascular grafts constructed in patients' subcutaneous spaces. However, since the formation of these vascular grafts depends on host health, their application is challenging in patients with suppressed regenerative ability. Therefore, the allogeneic implantation of grafts from healthy donors needs to be evaluated. This study aimed to fabricate allogeneic cardiovascular grafts in animals. Materials and methods: Silicone rod molds were implanted into subcutaneous pouches in dogs; the implants, along with surrounding connective tissues, were harvested after four weeks. Tubular connective tissues were decellularized and stored before they were cut open, trimmed to elliptical sheets, and implanted into the common carotid arteries of another dog as vascular patches ( n  = 6); these were resected and histologically evaluated at 1, 2, and 4 weeks after implantation. Results: No aneurysmal changes were observed by echocardiography. Histologically, we observed neointima formation on the luminal graft surface and graft wall cell infiltration. At 2 and 4 weeks after implantation, α‐SMA‐positive cells were observed in the neointima and graft wall. At 4 weeks after implantation, the endothelial lining was observed at the grafts' luminal surfaces. Conclusion: Our data suggest that decellularized connective tissue membranes can be prepared and stored for later use as allogeneic cardiovascular grafts. Abstract : Decellularized tubular connective tissues were cut longitudinally (A), and were allo‐transplanted as arterial vascular patches (B). Inner surfaces of the patch grafts at 1 week after transplantation were covered with fibrin (C), at 2 weeks, the inner surfaces of the grafts were partially covered with neointima (white‐colored) near the anastomotic site (D), and at 4 weeks, the inner surfaces of the graft were almost completely covered with neointima (E).